Madonna and child the development of Christian symbolism. (Swan / Jones Productions, 1992)
Traces the origins and meaning of Christian symbols in Medieval culture and discusses changes -- artistic, historic & theological -- that influenced them. Focuses on the Incarnation cycle, including the Christmas story.